Quantitative pupillometry as a sensitive tool for detecting tumor-related mass effect in the posterior fossa: a prospective feasibility study comparing metastatic versus skull base lesions - Grutza, Martin; Mitschang, Dorothea; Sydorenko, Viktoriya; Dugas, Martin; Krieg, Sandro; Lenga, Pavlina (Journal of neuro-oncology, 2026)
Objectives: Early and precise assessment of tumor-related mass effect is critical for surgical decision-making in patients with posterior fossa tumors, where even subtle elevations in intracranial pressure (ICP) may rapidly precipitate neurological decline. While quantitative pupillometry (QP) has demonstrated robust predictive capability for ICP-related deterioration in traumatic brain injury, its clinical utility for assessing neuro-oncological mass effects remains unexplored. This study aims to determine whether QP can reliably detect subtle neurological dysfunction related to mass effect in posterior fossa tumors, distinguishing specifically between metastatic and benign skull base lesions. Methods: We prospectively analyzed 58 adults (mean age 55.6 ± 13.8 years, 60.3% female) who underwent microsurgical resection of posterior fossa tumors from January to May 2025. Pupillary function was evaluated pre- and postoperatively using the automated NPi 200® Pupillometer. Pupillary parameters included the Neurological Pupil Index (Npi), constriction and dilation velocities, and latency. Clinical and radiological data, including tumor volume, midline shift, and Evans Index, were correlated with pupillometry metrics. Patients were categorized into metastatic (n = 21) and benign skull base (n = 37) tumor groups for subgroup analysis. Results: Benign tumors (55.2%) predominated, with skull base tumors significantly more often associated with cranial nerve deficits compared to metastases (p = 0.0023). Baseline pupillometric values appeared generally within normal range (median NPi = 4.4). However, significant postoperative improvements in pupillary parameters, including constriction velocity and NPi, occurred exclusively in skull base tumors. Preoperatively, NPi negatively correlated with tumor volume (ρ=–0.72, p = 0.008), while constriction velocity positively correlated with tumor volume (ρ = 0.73, p = 0.007) and midline shift (ρ = 0.60, p = 0.040). Latency correlated significantly with ventricular enlargement (Evans Index; ρ = 0.58, p = 0.046). Multivariate analysis confirmed tumor volume as an independent predictor of impaired NPi (β=–0.021, p = 0.015). Furthermore, in an exploratory ROC analysis among patients with skull base tumours, a preoperative NPi < 4.0 was associated with meaningful postoperative pupillary recovery (AUC = 0.81, 95% CI: 0.64–0.94) in this cohort. Conclusions: Quantitative pupillometry, particularly the NPi and constriction velocities, sensitively identifies early neurological impairment from posterior fossa tumour–related mass effect. Moreover, lower preoperative NPi values were associated with postoperative neurological improvement, suggesting that pupillometry may have potential as a bedside tool to support surgical decision-making; however, these exploratory findings require validation in larger cohorts before firm predictive claims can be made.”
Online veröffentlicht: 08. Dezember 2025
Gesehen am 24.02.2026